Multi-objective optimisation method for coordinating battery storage systems, photovoltaic inverters and tap changers - Hashemipour, N.; Aghaei, Jamshid; Lotfi, Mohamed; Niknam, Taher; Askarpour, Mohammad; Shafie-khah, Miadreza; Catalão, Joao P.S. (IET, 2020)
The many well-established advantages of distributed generation (DG) make their usage in active distribution networks prevalent. However, uncontrolled operation of DG units can negatively interfere with the performance of other equipment, such as tap-changers, in addition to resulting in sub-optimal usage of their potential. Thus, adequate scheduling/control of DG units is critical for operators of the distribution system to avoid those adverse effects. A linearised model of a multi-objective method for coordinating the operation of photovoltaics, battery storage systems, and tap-changers is proposed. Three objective functions are defined for simultaneously enhancing voltage profile, minimising power losses, and reducing peak load power. The formulated multi-objective problem is solved by means of the epsilon-constraint technique. A novel decision-making methodology is offered to find the Pareto optimality and select the preferred solution. To assess to proposed model's performance, it is tested using 33-bus IEEE test system. Consequently, tap-changers suffer lessened stress, the batteries state-of-charge is kept within adequate limits, and the DG units operation is at higher efficiency. The obtained results verify the effectiveness of this approach.
Keywords: multi-objective optimization; battery storage systems; photovoltaic inverters; tap changers; distribution networks; electrical power networks; distribution of electricity; voltage; distributed systems; electrical engineering; electric power; distributed generation; transmission of electricity; reactive power; optimisation; fi=Sähkötekniikka|en=Electrical Engineering|